On alternative interest rate processes - Dahlquist, Magnus (Journal of Banking & Finance, 1996)
In this paper alternative interest rate processes are estimated for Denmark, Germany, Sweden, and the UK, using the generalized method of moments (GMM). In line with the study by Chan, Karolyi, Longstaff, and Sanders (1992) on US data, there seems to be a positive relation between interest rate level and volatility for some countries. In contrast to their study, it is found that mean-reversion plays an important role for the specification of the interest rate dynamics. The results seem to be robust to the use of different moment conditions, and simulations of the estimated models reveal that they are fairly able to capture non-fitted moments as well. In addition, there is evidence of a structural change in the Danish interest rate process in August 1985, which may be due to a change in monetary policy. The small sample properties of the GMM estimators are also studied through simulations.